The Scars that Never Heal: Identifying Projectile Point Manufacturing Techniques from Flake Scars: A Case from Cedar Mesa, Utah. (December 2014) - Morin, Jesse; Matson, R.G.
Abstract : Geib has recently argued that there are major differences between the ways that Archaic and Basketmaker II (BM II) peoples made projectile points, namely that BM II peoples used indirect punches and wide compound pressure flakers to produce very thin, broad bifaces. We build on this analysis by measuring six attributes related to flake scar morphology on samples of Archaic and BM II bifaces from Cedar Mesa, Utah. The differences between the two groups for each variable are strongly statistically significant. Metric multidimensional scaling of these attributes reveals clear differences between Archaic and BM II bifaces based on flake scars and also allows us to detect previously misclassified artifacts. We suggest that the BM II tradition of making bifaces and points with indirect punches and compound flakers is an example of enculturated style.